MASS PRODUCTION OF ENTOMOPATHOGENIC NEMATODES OF LOCAL ISOLATES AS BIOLOGICAL CONTROL AGENTS OF COFFEE BERRY BORER (HYPOTHENEMUS HAMPEI FERR.) - Wagiyana, Wagiyana; Sulistyanto, Didik; Waluyo, Joko (Universitas Lampung, 2019)
Entomopathogenic Nematodes (EpNs) that serve as biological control agents include Steinernema spp and Heterorhabditis spp. EPNs Heterorhabditis indicus (Bromo Isolate) has a high toxicity against larvae Lepidoptera and Coleoptera and was successfully developed for mass production in Biological Control Laboratory of Jember University. These nematodes will be formulated as solid and liquid biopesticides. This research aims: to find EPNs local isolates from smallholder coffee plantations; to identify local and in vivo and in vitro cultured EPNs isolates; to determine the pathogenicity of EpNs local isolate against Coffee Berry Borrer (CBB) Hypothenemus hampei Ferr and to formulate EpNs in vitro culture as a liquid and solid formula. These formula were tested for the patogenicity and viability of EpNs to the larvae of H. hampei, Tenebrio molitor and Galleria melonella. The results showed that the pathogenecity of EpNs isolate to the larvae of CBB in Silo was 30% after 24 hours and 90% after 48 hours of in vivo inoculation. However, the mortality of CBB larvae was only 10% by liquid spraying on the coffee berry. The viability was 524 IJ (Infective Juvenile) on liquid formula packed on polyurethane sponge, and this was higher than that on solid formula (330 IJ).